THE EFFECTIVENESS OF MICRO-INFLUENCER ENDORSEMENTS IN INCREASING CONSUMER PURCHASE INTEREST - Andi Hajar; Andi Kamariah; Alifia Khansa Daffina; Rahmatia Nur Iftitah (Media Inovasi Pendidikan dan Publikasi, 2026)
This research aims to analyze the effectiveness of micro-influencer endorsement strategies in increasing consumer purchase interest on the @Styleroomm.co Instagram account in Makassar. The primary focus of this study is to evaluate how visual elements, the use of local dialects, and information transparency through video influence digital audience behavior. The method used in this research is descriptive qualitative, with data collection techniques including open-ended questionnaires distributed to 12 respondents and in-depth interviews with key informants. Scientific findings indicate that the influencer's self-presentation through makeup and content aesthetics acts as the primary stimulus in triggering initial audience attention (stop scrolling). Furthermore, the use of the Makassar local dialect (particles 'ji', 'mi', and 'ki') serves as an instrument of honesty validation that strengthens message credibility and emotional proximity. The findings also confirm that visual transparency in video content is more effective in reducing consumer skepticism compared to static catalog photos. The conclusion of this research is that the synergy between local cultural identity and visual production quality is the key factor in converting audience attention into actual purchase intent.